ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN TOKO ELEKTRONIK MENGGUNAKAN METODE K-NEAREST NEIGHBOR - Fenny Purwani; Marlinggi Marlinggi; Defri Henzen Heriawan; M Kevin Rizki Pratama; Rio Ananda Pratama (Jurnal Riset Teknik Komputer, 2024)
This study aims to analyze and design a web-based sales information system for the Bakri Electronics Store. With the advancement of information technology and the internet, many companies have begun adopting web-based systems to facilitate their business processes. Currently, Bakri Electronics Store relies on manual transactions, requiring customers to visit the store in person. This research proposes an online sales system that allows customers to browse products, make purchases, and complete payments online, thereby expanding market reach and improving operational efficiency. The research methods used include interviews with the store owner and manager, as well as direct observations. The system is designed using the PHP platform with a MySQL database and hosted on AWS, providing real-time information on product availability, pricing, promotions, as well as payment and shipping processes. The implementation of this system is expected to enhance sales and customer convenience, while strengthening the interaction between sellers and buyers.